KETERKAITAN KATEGORI KEPEMIMPINAN DENGAN ENAM KATEGORI LAINNYA DALAM MALCOLM BALDRIGE CRITERIA FOR PERFORMANCE EXCELLENCE (MBCFPE) PADA BADAN USAHA MILIK NEGARA - Rudjito Rudjito; Arief Daryanto; Sjafri Mangkuprawira; Noer Azam Achsani (School of Business, Bogor Agricultural University (SB-IPB), 2010)
Some State Own Enterprises (SOEs) have measured their performance based on Malcolm Baldrige Criteria for Performance Excellence method yearly since 2005 and participated in Indonesia Quality Award (IQA) to recognize their performances. The MBCfPE method measures company performance based on seven criterion categories, which Leadership as the first category is stated in the method that must be visionary, motivator and as the driver to lead people and entire organization to achieve performance excellence. The purposes of this study is to analyze the interrelatation of Leadership as first category to category second up to category seventh of MBCfPE.Convenience and purposive (judgmental) sampling techniques are used to choose twelve SOEs, which consist of two groups of six SOEs: “Good Performance” and “Below Good Performance”. Two hundred seventy two respondents consist of SOEs’ CEO, management and employees who understand MBCfPE method have participated in this study which selected by judgmental sampling technique. Reseacher used Rank Spearman and Discriminant anlysis for analyzing the interrelation of leadership category to category second up to seventh of MBCfPE. According to rank-spearman correlation analysis results, in overall, most of variables X (areas to address of Laedership category), have relation with variables Y (areas to address of category second up category seventh of MBCfPE, except for variable X4 (Legal and ethical behavior) and variable X5 (Societal Responsibility and Support of key communities) to variable Y1 (Strategy development process). From Discriminant analysis, it can be concluded that Communication and Company Performance is variable that discriminate between SOEs “Good Performance” and SOEs “Below Good Performance”.